Foraging preferences of captive Canada geese related to turfgrass mixtures - Washburn, Brian E.; Barras, Scott C.; Seamans, Thomas W. (DigitalCommons@University of Nebraska - Lincoln, 2007)
Overabundant populations of Canada geese (Branta canadensis) cause economic and safety concerns associated with collisions with civil and military aircraft. Habitat management techniques that reduce the use of airfield habitats by geese might reduce these concerns. The objective of this study was to determine if captive Canada geese exhibited a foraging preference between a vegetation mixture consisting mostly of perennial ryegrass (Lolium perenne) and white clover (Trifolium repens) versus an endophyte-infected tall fescue- (Festuca arundinacea) based vegetation mixture. We established 6 paired plots of perennial ryegrass-dominated and tall fescue-dominated mixtures at NASA Plum Brook Station in north-central Ohio during 2000. Behavioral observations of captive Canada geese were conducted during 2001 and 2003. In 2001, ryegrass plots contained 4% perennial ryegrass and 94% white clover. Fescue plots contained 72% tall fescue and 6% clover. The numbers of geese observed in ryegrass plots (Χ̅ = 2.0 geese/plot, SE = 0.35) and tall fescue plots (Χ̅ = 1.9 geese/plot, SE = 0.33) were not different (F1,10 = 0.03, P = 0.86). Foraging by captive Canada geese was similar (F1,10 = 0.26, P = 0.62) in the perennial ryegrass plots (Χ̅ = 12.8 bill contacts/minute/4 geese, SE = 1.4) and the tall fescue plots (Χ̅ = 11.2 bill contacts/minute/4 geese, SE = 2.9). In 2003, ryegrass plots contained 42% perennial ryegrass and 20% white clover. Fescue plots contained 91% tall fescue. The number of captive geese observed in ryegrass plots (Χ̅ = 3.0 geese/plot, SE = 0.1 9) was greater (F1,10 = 56.9, P -50.001) than in the fescue plots (Χ̅ = 1.0 geese/plot, SE = 0.19). Foraging by Canada geese was greater (F1,10 = 346.5, P ≤ 0.001) in the ryegrass plots (Χ̅ = 30.7 bill contacts/minute/4 geese, SE = 1.55) than in the tall fescue plots (Χ̅ = 0.8 bill contacts/minute/4 geese, SE = 0.41). Our findings suggest tall fescue might be a favorable species to be used in reseeding and vegetation renovation projects in areas where Canada geese are a ...